Religious and Industrial Education in the Nineteenth-Century Magdalene Asylums in Scotland - Thor, Jowita (Studies in church history, 2019)
The Magdalene Asylums were penitentiaries for ‘fallen’ women. A high percentage of such women had been involved in sex trade in some form; others were betrayed fiancées, unmarried partners or women with drinking problems. This article explores the Magdalene Asylums’ education as a tool for reforming the inmates into women reflecting the managers’ ideals of femininity and Christian virtue in nineteenth-century Scotland. The reports of these institutions describe their aims, quoting selected letters of former inmates, their parents and new employers. They give us an insight into how these Christian philanthropists imagined and applied educational programme for this group of women and girls. The two main areas of the asylums’ education were religious teaching and instruction in a range of skills necessary for becoming a servant or a factory worker. Those who could not read and write also received basic literacy lessons. Magdalene Asylums in nineteenth-century Scotland offer a rich case study of a context in which education had a very narrow meaning and served a precisely defined purpose. They provided a broad spectrum of skills, although never at a comprehensive level. The article explores the managers’ intentions and ideals by analysing the language they used to talk about ‘successfully reformed’ women.